Adolescent texter profile, autonomy, and identity. - Onga, Madonna Faith
This study examined the profile of edolescent texters and its relationship to their level of autonomy and identity status. the respondents were students from Iloilo National High School. A total of 160 students from each year level completed a take home set of qustionnaires namely the profile texters, CASE and Modified EOMEIS. The results showed that age of the respondents when they first acquired cell phones were related to their autonomy but not to their identity status. On the other hand, the frequency of their sent and received messages of the respondents was not related to their level of autonomy and identity status.